Genetic hauntings: Mediating pre-patienthood and haunted health on TV - Schmidt Nielsen, Ann-Katrine; Stage, Carsten (MedieKultur: Journal of media and communication research, 2023)
Through the development of a “health hauntological” approach, this article investigates how pre-patient illness narratives are mediated and negotiated in and around the DR documentary series Gentesten ændrede mit liv (2020) [The gene test changed my life]. We argue that this documentary format attests to how the expansion of genetic testing technologies alters experiences, genres, and narratives of illness that increasingly move to a pre-diagnostic and pre-symptomatic domain. The analysis shows how the use of genetic testing technologies creates hauntological situations in which pre-patients – through the mapping of family pathologies of the past and possible future diagnoses – encounter the complex temporalities and entanglements inherent to genetic bonds. Furthermore, we claim that these haunting encounters with mortality, vulnerability, and potential loss can be acted on – or listened to – in various responsive ways. Mediating pre-patient illness narratives thus entails an ethical balancing between care for participants and the desire for tellable, transformational narratives.